Prevalence and Clinical Aspects of Otodectes cynotis Infestation in Dogs and Cats in the Semi-arid Region of Paraíba, Brazil - Silva, Juliana Trajano; Ferreira, Larissa Claudino; Fernandes, Mikaelly Mangueira; Sousa, Larissa Nascimento; Feitosa, Thais Ferreira; Braga, Fabio Ribeiro; Brasil, Arthur Willian de Lima; Vilela, Vinícius Longo Ribeiro (Acta Scientiae Veterinariae, 2020)
Background: Infestation by Otodectes cynotis is one of the main causes of external otitis in small animals, causing great disconfort and predisposition to secondary bacterial or fungal infections, with relevant importance in the small animal medicine. In dogs, a small number of this parasite in the ears may cause inflammation, while in cats, otoacariasis accounts for half of the external otitis cases. Due to the insufficiency of data about the prevalence of this disease in the Northeast region of Brazil, the purpose of the present study was to evaluate the prevalence and clinical aspects of O. cynotis in dogs and cats from the Semi-arid region of Paraíba, Brazil. Material, Methods & Results: The research was conducted in the municipality of Sousa, Paraíba State, Brazil. A total of 102 dogs and 152 cats had their external ear canals examined by bilateral otoscopy, using an otoscope with a veterinary cone that allows inspection of the external ear canal. Parasitological swabs were also used to determine the prevalence of parasitism by O. cynotis. Samples collected in swabs were stored in a 70% alcohol preservative solution and sent to the Laboratory of Veterinary Parasitology, in wich were examinated on direct research, using microscopes in the 10x objective (magnification of 100x). In all animals, clinical examinations were performed and their owners answered an epidemiological questionnaire to collect information about food and sanitary management. During the clinical examination, characteristics such as otopodal reflex, and the presence of pruritus and/or cerumen were also evaluated. The prevalence of dogs and cats positive for O. cynotis was 33.3% (34/102) and 52.6% (80/152), respectively. Bilateral infestations occurred in 52.9% (18/34) of the positive dogs. Most of the positive animals showed evidence of the mite in both tests, Otoscopy + Swab (dogs: 58.8% - 20/34, cats: 66.2% - 53/80). Discussion: A high prevalence of O. cynotis infestation was observed in dogs (33.3%) and even higher prevalence in cats (52.6%), both are higher than it was expected. The diagnosis methods were effective for detecting infestation by this parasite, and the parasitological swab resulted in higher diagnosis rate than the otoscopy. The use of two diagnosis methods resulted in a greater number of positive diagnoses, explaining the high prevalence found in the present study. A higher prevalence was observed for animals that had contact with other animals. The direct form is the most accepted mode of transmission of Otodectes sp. and close confinement of animals was considered the main associated factor for frequent reinfestation by the mite. For dogs, the presence of cerumen and pruritus were seen as O. cynotis infestation factors. Considering dogs, in the clinical examination, the presence of pruritus was significantly associated with the occurrence of parasitism. This association can be explained because O. cynotis is very active within the ear canals of parasitized animals, causing great annoyance and pruritus. No statistically significant risk factors were found for cats, but it was observed that adults had higher levels of infestation when compared to young cats, wich was not expected, as the literature commonly reports that young cats have higher levels of infestation. This can be explained by the confinement and the usual direct contact by different cats, increasing the occurrence of the parasite. In cats, the clinical examinations showed that the presence of otopodal reflex was significantly associated (p<0.2) with the parasitism occurrence (55.4%; 66/119). The evaluation of this reflex has been considered as one of the symptoms of otocariosis.